A Study of Calendar Effect on Stocks in the BSE Sensex - Avil Saldanha; Rajendra Desai, (International Journal of Management Studies (IJMS), 2021)
The primary objective of this research paper is to find whether calendar effect exists in the BSE Sensex. Calendar effect shows the disparities in stock prices in the stock market subsequent to certain trends based on various time periods of year, various time periods of the month, and various days of the week. This type of tendencies/regular patterns happen at a definite time period in any calendar year. We utilized BSE Sensex data for a period of twelve years, starting from 2005 to 2016 to explore possible patterns of buy-sell months that would result in a minimum level of profitability.